1980
DOI: 10.1007/bf01340537
|View full text |Cite
|
Sign up to set email alerts
|

A re-examination of the single radial haemolysis technique for the assay of influenza anti-neuraminidase antibodies in human sera

Abstract: A new study is described of the use of single radial haemolysis (SRH) for the measurement of antibodies to influenza virus neuraminidase (NA). The technique is known to be consistently successful in the assay of anti-haemagglutinin (HA) antibodies, subject only to the condition that the indicator virus belongs to an appropriate serotype. Its adaptation to the measurement of anti-NA is, however, more difficult. The virus used must be a recombinant which contains a specific NA and an "irrelevant" HA. However the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The diameter of the zone of hemolysis varied directly with the dilution of specific antiserum in the well, thus suggesting a proportional relationship between zone diameter and specific antibody concentration. This relationship similarly exists in SRH systems for hemagglutinating viruses (1,8,9,18,19,23). As previously reported by others (9,19,20), the slopes of the regression lines relating zone diameter and antibody concentration were equal for antisera of differing initial potencies.…”
Section: Discussionsupporting
confidence: 84%
“…The diameter of the zone of hemolysis varied directly with the dilution of specific antiserum in the well, thus suggesting a proportional relationship between zone diameter and specific antibody concentration. This relationship similarly exists in SRH systems for hemagglutinating viruses (1,8,9,18,19,23). As previously reported by others (9,19,20), the slopes of the regression lines relating zone diameter and antibody concentration were equal for antisera of differing initial potencies.…”
Section: Discussionsupporting
confidence: 84%
“…In a comparative study of MRC-3 and X-38 strains for RRH the latter virus appeared to be more appropriate. Strong correlation of antineuraminidase antibody titre was found between the results of RRH and other conventional techniques (Callow and Beare, 1980). Investigation of monoclonal antibody with RRH confirmed the diagnostic efficacy of the reaction.…”
mentioning
confidence: 56%
“…Specificity of ELISA for anti-N2 in human sera. Since it appeared that there was some crossreaction between NA subtypes by ELISA, seven of the pairs of sera were reacted with a recombinant possessing Ni, CDC-8 (H7N1), which was previously used successfully for recording anti-NA rises by NI and SRH in vaccinees given A/New Jersey/8/76 (HlNl) (6). At a dilution of 1/200, very low ODs were obtained; all were below the base-line value, as were the ODs when these sera were reacted in plates containing HlNl virus (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…NI and SRH. These tests were performed as described previously with the recombinant X-15 HK (6), except that in the present study SRH values are reported as zone areas, instead of diameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation